Pelayanan Kesehatan Virtual Pada Pasien Leukimia Selama Pandemi Covid-19 - Bambang Aditya Nugraha; Sulastini Sulastini; Sandra Pebrianti; Gusgus Ghraha Ramdhanie (Jurnal Medika Cendikia, 2021)
Covid-19 is an airborne disease. Thus, minimizing physical contact is an option in preventing the spread and transmission of Covid-19. contact from physical contact in leukemia patients is a delay in health services with the consideration that patients with leukemia experience a decrease in the immune system which can be comorbid when infected with covid 19. Efforts are made for leukemia patients to organize virtual tele health services to minimize physical contact between leukemia patients with COVID-19 patients in health facilities. The research method used is narrative review using Google Scholar and pubmed as the article database. The criteria for the inclusion of the article are that it was published during the COVID-19 pandemic, in Indonesian and in English, and the full text is available. The keywords used are virtual care, tele-nursing, leukemia and covid-19. The search results showed 374 articles, but only 5 (five) articles that matched the criteria and focus that had been set. It was found that virtual health services have the potential to be carried out in order to meet patient needs and prevent the spread and transmission of covid 19 in patients with leukemia. The search results are expected to be information related to alternative health services for leukemia patients during the pandemic in order to improve health status and quality of life.